Balloon Views of Source Code and Their Multiscalable Font Modes - Lin, Chun-Cheng; Yen, Hsu-Chun (IV'07: Proceedings of the International Conference on Information Visualisation, 2007)
The majority of program editors available on the market support the view of a directory-explorer style to display only those code lines of interest. Among them, the fisheye and the fractal views of source code (in which each line has a value reflecting the degree of interest and importance) have received a lot of attention in the literature. In information visualization, drawing trees based on fractal theory also plays an interesting role as the so-called balloon drawing of hierarchical data includes two models: the fractal and the SNS (subtrees with nonuniform sizes) models. It is therefore natural to consider a new source code visualization style based on the SNS model of balloon drawing. A main feature of the SNS view is that the value of each line reflects the number of its descendants when the source code is viewed as a tree structure. Unlike the view of a directory-explorer style, the multiscalable font mode (which was originally utilized in the fractal view of source code) displays all the lines in such a way that each line has the font size proportional to its value. In this paper, we investigate various issues concerning the multiscalable font modes of the fish-eye, the fractal, and the SNS views of source code, in hope of providing guidelines for the programmer to better comprehend the program code in practice.